The challenges of returning to face-to-face education in dentistry in the context of the covid 19 pandemic - Fukuhara, Mary (2022)
The restrictive measures to face the Covid 19 pandemic affected the normal development of various activities, including higher education, although the virtualization of the contents of the different courses was a measure to give continuity to education, in the case of sciences for health clinical practice in real conditions is essential for the student to achieve the skills required by this type of professional career, so the return to these activities is a great challenge since the conditions of this return are completely different from conditions before the pandemic. This article aims to reflect on the return to presential education and the challenges we must face to continue training dental professionals with academic excellence.